2020
DOI: 10.1111/plb.13169
|View full text |Cite
|
Sign up to set email alerts
|

Function and application of the Eutrema salsugineum PHT1;1 gene in phosphate deficiency stress

Abstract: Low availability of inorganic phosphate (Pi) in soil is often a limiting factor for plant growth and productivity. The Pi transporter plays an important role in the absorption and utilization of phosphorus in plants. Eutrema salsugineum shows strong tolerance under Pi stress conditions, but the function of the E. salsugineum PHT1 genes has not yet been systematically studied. This study isolated a phosphate transporter gene (EsPHT1;1) from the halophyte E. salsugineum and functionally characterized it in the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…4.3 | Substitution of P i with P from organic fertiliser hardly change ClaPHT1 members expression PHT1 genes encode high-affinity P i transporters to participate in P i acquisition, and the majority of PHT1 genes are expressed in both roots and shoots (Wang, Hoffland, Feng, & Kuyper, 2017;Yang, Zhao, & Wang, 2020). This study showed that ClaPHT1;2, ClaPHT1;4 and ClaPHT1;5 expression did not change in roots (Figure 6h,i,k) or leaves (Figure 7f,g,h) when P i was partially substituted by P from organic fertiliser.…”
Section: P Concentration and P Accumulation In Watermelonmentioning
confidence: 99%
“…4.3 | Substitution of P i with P from organic fertiliser hardly change ClaPHT1 members expression PHT1 genes encode high-affinity P i transporters to participate in P i acquisition, and the majority of PHT1 genes are expressed in both roots and shoots (Wang, Hoffland, Feng, & Kuyper, 2017;Yang, Zhao, & Wang, 2020). This study showed that ClaPHT1;2, ClaPHT1;4 and ClaPHT1;5 expression did not change in roots (Figure 6h,i,k) or leaves (Figure 7f,g,h) when P i was partially substituted by P from organic fertiliser.…”
Section: P Concentration and P Accumulation In Watermelonmentioning
confidence: 99%